Efficacy of knockdown insecticide based on Permot (Passiflora foetida L.) leaf extract against mortality of German cockroach (Blattella germanica L.) - Rina Priastini Susilowati; Flora Rumiati (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2021)
Chemical insecticides have a detrimental effect on not only the target species, but also on non-target species and the environment. Transfluthrin is a pyrethroid class II insecticide that is considered to be safe for humans. However, repeated use over an extended period of time can result in cockroach resistance. For this reason, this study sought out alternative materials, specifically Permot leaf (Passiflora foetida L.). This study aims to determine the neurotoxic efficacy of insecticides derived from Permot leaf extract on German cockroach knockdown time and death. A total of 120 German cockroaches and was replicated three times. After 1 h of exposure to insecticides containing transfluthrin 3000 ppm and Permot leaf extract up to a dose of 4000 ppm, knockdown time and cockroach death were observed. The probit test was used to determine the cockroach knockdown time. The study's findings indicated that when cockroaches were exposed to insecticides derived from Permot leaves at a dose of 4000 ppm, the knockdown efficacy was KT50 for 8 min and KT90 for 30 min. The blocking test on German cockroach spiracles established that exposure via cockroach spiracles was more effective than exposure via other cockroach organs in killing.